Kant and the universality of taste: form the pre-critical period to the Critique of the power of judgment - Miranda Sena, Carolina (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Kant's aesthetic and systematic investigation in search of the a priori principle of the faculty of judgment, which, among other things, would justify the universality and necessary validity without concepts of the judgment of taste, is the subject of investigation of the Critique of the Power of Judgment. However, before the writing of the third Critique, a work published in 1790, Kant's understanding of the foundation of a universality of taste, of an a priori principle for taste, and of the autonomy of judgments of taste and their relations with knowledge were undergoing changes. This brief essay aims to cover these changes in Kant's positions in relation to the universality of taste, its foundation and its apriority, from the pre-critical period, through some Reflections from the 1760s and 1770s, passing through the Critique of Pure Reason, a published work in 1781, arriving at the project of a Critique of the Power of Judgment announced in a letter to Reinhold in 1787.